การประเมินมูลค่าบริการของระบบนิเวศ บริเวณลุ่มน้ำคลองชุมพร จังหวัดระนอง และจังหวัดชุมพร - รื่นสุคนธ์ ธำรงค์; ไตรสุรัตน์ ยงยุทธ; ตั้งธรรม นิพนธ์; โตกฤษณะ เรื่องไร (วารสารวนศาสตร์ไทย, 2016)
Forest area in Klongchumphon Watershed has been converted to para-rubber, oil palm and fruit orchard. Deforestation causes changes in water yield and sediment load in the stream. Severe floods frequently occurred in down stream every year. The objectives of this research were to predict water yield, soil loss and to quantify economic value of nutrient depletion and sediment dredging in Klongchumphon Watershed, Ranong and Chumphon Province as the results of land-use change between 2012 and 2030. Three future land use scenarios were defined including 1) trends, 2) conservation, and 3) development. Geographic Information System (GIS), CLUE-S model, InVEST and USLE were used in this research. The results revealed that the scenario 1 increased area of para-rubber by 11.32 % and reduced forest area by 9.52 %. The converted forest was replaced by para-rubber by 7.73 %. In addition, the scenario 1 would provide annual water yield of 486.64 million m3 and generated sediment loss of 4.60 ton/rai/year. The cost to remove sediment out of the stream was 8.20 baht/rai. The estimated major nutrients loss (N-P-K) were 597.46, 0.01 and 0.22 kilogram/rai, respectively and the accumulated value of nutrients loss was 11,388 baht/rai. The scenario 2 slightly increased rubber plantations (2.30 %) and forest area was stable. It generated annual water yield of 480.16 million m3 and sediment loss of 4.07 ton/rai/year. The cost to dredging was 7.27 baht/rai. The estimated major nutrients loss (N-P-K) were 529.47, 0.01 and 0.19 kilogram/rai respectively and the accumulated value of nutrients loss was 10,092 baht/rai. The land-use scenario 3 substantially most reduced forest cover by 18.32 % and 9.91 % was converted to rubber plantations. The predicted annual water yield was 494.92 million m3 and the sediment load was 5.07 ton/rai/year. The cost to remove sediment in the stream channel (8.97 baht/rai) and the accumulated value of major nutrients loss (12,455 baht/rai) were the highest among the three land-use scenarios. Based on these findings, the land-use scenario 2 is appropriate for Klongchumphon Watershed because it would generated the least soil erosion and economic loss of soil fertilizers.